The Distinctive Qur’anic Manuscript of Nāfiʿ’s Qirāʾah Transmitted by Qālūn in the Sang Nila Utama Museum, Riau: A Philological Study - Afriadi Putra; Maharsi; Adib Sofia (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
Qur’anic manuscripts preserve material evidence of copying practices and reading traditions. This article analyses Qur’anic manuscript 07.15/2017 in the Sang Nila Utama Museum, Riau, which records the qirāʾah of Nāfiʿ transmitted by Qālūn. Using a qualitative philological approach, the study combines codicological description with a textological examination of reading variants. The codicological analysis covers the manuscript’s paper, watermark, dimensions, textual arrangement, illumination, and dated colophon. Juz 30 is used for the textological analysis because the relevant folios are legible and contain numerous points at which canonical readings differ. The manuscript comprises 863 pages, begins at Q 3:82, and contains several displaced or missing folios. Its colophon names Ibrāhīm bin Aḥmad bin Aḥmad bin al-Amīn al-Khalīl, a Shāfiʿī from Zabīd, and dates completion to 4 Jumādā al-Ūlā 1153 AH (28 July 1740 CE). The analysed portion records four groups of morphological variants and twenty-seven phonological forms associated with Qālūn’s transmission. Because the examination is limited to Juz 30, the findings establish the reading pattern only for that section. The manuscript nevertheless provides material evidence that Nāfiʿ–Qālūn readings circulated within the wider manuscript environment of the Malay world alongside the region’s more common ʿĀṣim–Ḥafṣ tradition.